2012
DOI: 10.3310/hta16040
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive diagnostic assessment tools for the detection of liver fibrosis in patients with suspected alcohol-related liver disease: a systematic review and economic evaluation

Abstract: An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per issue and for the rest of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 116 publications
0
43
0
Order By: Relevance
“…In particular, the cost of each strategy should be evaluated carefully in relation to the final clinical outcomes. Although few data are available on the costeffectiveness of different noninvasive strategies for detecting liver fibrosis [25], it is conceivable that methods incorporating a TE examination would be more costly than a simple score such as NFSA. From a purely clinical standpoint, it is obvious that the most effective method is FibroMeter VCTE in NAFLD Dincses and Yilmaz www.eurojgh.com the one that can detect the highest number of patients with severe fibrosis with maximum accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the cost of each strategy should be evaluated carefully in relation to the final clinical outcomes. Although few data are available on the costeffectiveness of different noninvasive strategies for detecting liver fibrosis [25], it is conceivable that methods incorporating a TE examination would be more costly than a simple score such as NFSA. From a purely clinical standpoint, it is obvious that the most effective method is FibroMeter VCTE in NAFLD Dincses and Yilmaz www.eurojgh.com the one that can detect the highest number of patients with severe fibrosis with maximum accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this score is quite adequate for populationbased studies and for clinical screening and follow-up purposes. 17,84,85 Despite recent developments in noninvasive methods for assessing NAFLD, liver biopsy remains the gold-standard method for diagnosing and characterizing it, since it may provide a nuanced evaluation that no other method is capable of today. On the other hand, it is expensive and highly invasive, and carries significant risk of morbidity and even mortality.…”
Section: -84mentioning
confidence: 99%
“…Stevenson et al [158] have conducted a systematic review and an economic evaluation of the diagnostic accuracy, cost-effectiveness and effect on patient outcomes of four non-invasive tests for liver fibrosis in patients with suspected alcohol-related liver disease. These tests include the ELF, FibroTest, FibroMAX and TE.…”
Section: Cost-effectiveness Of Non-invasive Markers For Liver Fibrosismentioning
confidence: 99%
“…These tests include the ELF, FibroTest, FibroMAX and TE. The authors concluded that no conclusive result could be provided on the most cost-effective strategy until further data are available [158]. Canavan et al [159] used a Markov decision analytic model to simulate a hypothetical cohort of 10,000 patients with chronic HCV initially without fibrosis over their lifetime and reported the cost-effectiveness of annual surveillance for cirrhosis in patients with chronic HCV.…”
Section: Cost-effectiveness Of Non-invasive Markers For Liver Fibrosismentioning
confidence: 99%